Role of Food Tradition in Conserving Crop Landraces On-Farm - Rijal, Deepak Kumar (Journal of Agriculture and Environment, 2010)
Local knowledge of crop diversity linked to food traditions, local practices and social norms is documented acquired through interaction with farmers and focus group discussion. Cooking quality of different rice varieties was assessed to see the effects of the environment factors. Different food dishes were assessed by trained cook, urban and rural consumers to identify dishes for market promotion. Diversified food traditions show close links to richness of crop landrace diversity. Crop landraces have substance, symbolic and sign values. Certain food dishes are used as symbolic offerings to different Gods such as lineage God, goddess and spirits of the past ancestors. Of the elaborated dishes tried, taro when prepared with legumes, mutton and fish, was preferred. Such preference was also landrace specific. 'Hattipow' for fried mutton, 'Panchamukhe' with fish and 'Ujarka' for Samosa are preferred. Culinary characters on rice landraces were unaffected by environment factors. The quality of improved variety, however decreased when grown in alien environments. The likelihood of crop landraces to be conserved increases if: a) they are competitive to other options farmers-custodian have b) farmer-custodian and consumers follow socio-cultural norms, and c) traditional dishes still remain popular. Increased demand for landraces and the promotion of landraces derived products help generate income and green jobs which are the same time offers of community incentives to conserve crop landraces on-farm. Key words: Dishes; Landraces; Livelihoods; Traditions; Values The Journal of AGRICULTURE AND ENVIRONMENT Vol. 11, 2010 Page: 107-119 Uploaded date: 16 September, 2010